Effects of immunisation against PCSK9 in mice bearing melanoma - Momtazi-Borojeni, Amir Abbas (Arch Med Sci, 2019)
INTRODUCTION: Inhibition of proprotein convertase subtilisin/kexin 9 (PCSK9) is an established modality for the treatment of hypercholesterolaemia. However, the impact of PCSK9 inhibition in other situations such as cancer remains largely unknown. The current study was conducted to study the effects of PCSK9 inhibition on cancer endpoints in mice bearing melanoma. MATERIAL AND METHODS: To generate antiPCSK9 antibody in vivo, a nanoliposomal antiPCSK9 vaccine adsorbed to 0.4% Alum adjuvant was subcutaneously injected in C57BL/6 mice four times with bi-weekly intervals. Two weeks after the last immunisation, mice were subcutaneously inoculated with B16F0 melanoma cells. After a tumour mass was palpable (approximately 10 mm(3)), the mice were randomly divided into four groups and subjected to different treatment protocols: (1) PBS (untreated control), (2) vaccine group, (3) the combination of vaccine and a single dose of liposomal doxorubicin (Doxil(®)), and (4) liposomal doxorubicin (positive control) group. To determine therapeutic efficacy, mouse body weight, tumour size, and survival were monitored every three days for 36 days. RESULTS: The nanoliposomal antiPCSK9 vaccine was found to efficiently induce specific antibodies against PCSK9 in C57BL/6 mice, thereby reducing plasma levels and function of PCSK9. Tumour volumes in the vaccinated group were not significantly different from those in the liposomal doxorubicin, combination, and control groups. The time to reach endpoint (TTE) values of the vaccine (28 ±5 days), combination (30 ±6 days), liposomal doxorubicin (34 ±2 days), and control (31 ±2 days) groups were not significantly different, either. Furthermore, the tumour growth delay (TGD) values of the vaccine (–11.5 ±15.4%), liposomal doxorubicin (7.75 ±6.5%), combination (–6 ±20.77%), and control (0 ±7.5) groups were not significantly different. Finally, there was no significant difference between the median survival time and lifespan of the vaccinated versus other tested groups. CONCLUSIONS: The nanoliposomal PCSK9 vaccine did not adversely affect the growth of melanoma tumour nor the survival of tumour-bearing mice.